Optimizing query execution in large differential factbase - Foo, Chuan Sheng (Nanyang Technological University, 2022)
Differential factbase is a uniform exchangeable representation supporting efficient querying and manipulation, based on the existing concept of program facts. Such factbase is used to store relevant information of software changes. However, the existing factbase is not designed to scale.